MULTI-STAGE PLASTIC SURGERY FOLLOWING MASSIVE WEIGHT LOSS: SEQUENCING OF FACE, NECK, BROW, AND EYELID LIFTS - INDICATIONS AND TECHNIQUES - Zuzanna Olga Reklewska,; Maja Osuch,; Maciej Osuch,; Olga Tatarata,; Martyna Jaciubek,; Carmena Luty,; Amanda Abramowicz,; Magdalena Rumin,; Anna Kiełboń,; Kornelia Domagała, (International Journal of Innovative Technologies in Social Science, 2026)
Background: Massive weight loss (MWL) following bariatric surgery or medical interventions results in significant soft tissue facial changes characterized by accelerated facial aging, fat devolumization, and increased skin laxity (American Society for Metabolic and Bariatric Surgery, 2019; Tan et al., 2022; Jafar et al., 2024; Shrivastava et al., 2008). These anatomical alterations necessitate specialized surgical approaches distinct from conventional facial rejuvenation procedures (Humphrey & Lawrence, 2023; Tay, 2023).Objective: This literature review aims to synthesize current evidence on multi-stage facial plastic surgery in post-bariatric patients, focusing on the sequencing, indications, and techniques for face, neck, brow, and eyelid lifts.Methods: A comprehensive literature review was conducted examining peer-reviewed publications from 2015-2025 in PubMed, Web of Science, Scopus, and other databases. Search terms included "massive weight loss," "facial rejuvenation," "post-bariatric surgery," "facelift," "neck lift," "brow lift," "blepharoplasty," and "sequencing." Studies addressing facial anatomical changes, surgical techniques, outcomes, complications, and staging strategies were included.Results: MWL patients demonstrate distinct facial changes including 88% midface volume loss, 82% platysma band formation, 60% perioral volume loss, and significantly increased neck skin laxity compared to non-MWL patients (Narasimhan et al., 2015; Couto et al., 2015). Extended SMAS facelift with platysmaplasty represents the preferred surgical approach, requiring approximately twice the volume of fat augmentation (22 mL vs. 12 mL) compared to traditional patients (Narasimhan et al., 2015). Current evidence suggests prioritizing face/neck lift as the primary procedure, with staged or concurrent upper facial rejuvenation (brow lift, upper blepharoplasty) based on individual anatomical assessment (Cabbabe, 2016; Narasimhan et al., 2015; Couto et al., 2015). Lower blepharoplasty is often deferred to reduce complication risk (Patrocinio et al., 2015; American Society of Plastic Surgeons, 2024). Patient selection criteria include weight stability for 12-18 months, BMI